Eufemisme dalam Novel Layangan Putus Karya Mommy Asf - Yunda Mardani, Ifra; Asnawi, Asnawi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
Euphemisms, as a form of softening words to replace taboo language, are an intriguing phenomenon worthy of study. Euphemisms arise in response to the need for more polite expressions in society. The use of euphemisms is not only limited to everyday conversations but is also often found in literary works such as novels. In this study, the focus is on the formation and benefits of euphemisms found in the novel "Layangan Putus" by Mommy Asf, using the theoretical framework proposed by Sutratman (2017). A descriptive method is used with a hermeneutic approach. The data analyzed are words or phrases containing euphemisms in the novel. The results of the study show five common forms of euphemism formation, including the use of abbreviations, loanwords, foreign terms, metaphors, and periphrasis. The most dominant form found is the use of foreign terms, perhaps because there are still many sentences containing foreign terms unfamiliar to the general readership in the novel.